Initial Public Offerings in the UK, USA and Japan. - Jenkinson, T (CEPR, 1990)
When a firm makes an initial public offering (IPO) of its equity, the accuracy with which its shares are priced will be an important factor determining the cost of "going public". This paper compares the accuracy of IPO pricing in the United States, United Kingdom and Japan over the period 1985-88. It is found that IPOs are systematically priced at a discount relative to their subsequent trading price in each count.